Evaluasi laporan keuangan untuk menilai kinerja keuangan pemerintah daerah Simalungun - Sahala Purba; Maria Astuti Br Gurusinga; Wilfredo Nahulae; Herlin Tresia Perbina Br Sitepu (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2024)
Based on the following metrics: (1) Regional Financial Independence Ratio, (2) Regional Financial Dependency Ratio, (3) Fiscal Decentralization Degree Ratio, (4) Original Income Effectiveness Ratio Regional, (5) Regional Original Income Efficiency Ratio, (6) Regional Tax Effectiveness Ratio, (7) Regional Tax Efficiency Ratio, and (8) BUMD Contribution Degree Ratio, this study attempts to analyze the financial performance of the Simalungun Regency Government in the 2013–2022 budget year. Data was gathered using a sampling technique. The results of the analysis show that the Simalungun Regency has a low Regional Financial Independence Ratio, and the region still depends on the central government. The Regional Financial Dependency Ratio is relatively low, and Simalungun still depends on external parties. Moreover, The Ratio of the Degree of Fiscal Decentralization is classified as low; The Ratio of the Effectiveness of regional owned-sources Income is classified as less effective; The Regional owned-sources Income Efficiency Ratio is very efficient; Tax Effectiveness Ratio is classified as quite effective; The Regional Tax Efficiency Ratio is classified as very efficient, and The Ratio of the Degree of Contribution of Regional Owned enterprise is classified as low.